Effect of mineral and organic fertilization on growth and productivity of garlic plant - tafah, Rana (Latakia University Journal -Biological Sciences Series, 2019)
The experiment was carried out in the village of Sarna in the area of ​​Slonfeh in Lattakiagovernorate during the agricultural season (2017-2018)to study the effect of different types of mineral and organic fertilizers on the growth and productivity of garlic, was followed the design of complete random sectors and included three treatments: 1-Treatment of chemical fertilization (control), 2- Treatment of organic and chemical fertilization, 3- Treatment of organic fertilization. The results showed that the treatment of organic fertilizer in poultry manure was higher in terms of plant height, where the plant height was 74.6 cm and the production amount was 1293 kg / acres, compared to 1077 ,1168 kg / acres in mineral fertilization treatment and mineral with organic fertilization treatment respectively. The differences were not significant in the number of leaves on the plant and the number of cloves in the head of garlic نفذ البحث في قرية صرنا التابعة لناحية صلنفة بمحافظة اللاذقية وذلك خلال الموسم الزراعي لعامي( 2017-2018) لدراسة تأثير أنواع مختلفة من السماد المعدني والعضوي في نمو وإنتاجية الثوم ، اتبع تصميم القطاعات العشوائية الكاملة وشمل البحث ثلاث معاملات : 1- معاملة تسميد كيميائي (شاهد)،2- معاملة تسميد عضوي وكيميائي ،3- معاملة تسميد عضوي. بينت النتائج تفوق معاملة التسميد العضوي بزرق الدواجن من حيث ارتفاع النبات حيث بلغ ارتفاع النبات74.6 cm وكمية الإنتاج 1293كغ/دونم مقابل ,10771168كغ/دونم في معاملتي التسميد المعدني ، والتسميد المعدني والعضوي بالترتيب . ولم تكن الفروق معنوية في عدد الأوراق على النبات وعدد الفصوص في رأس الثوم .